2019
DOI: 10.1111/anae.14959
|View full text |Cite
|
Sign up to set email alerts
|

Low‐flow apnoeic oxygenation for laryngeal surgery: a prospective observational study

Abstract: Summary Laryngeal surgery requires a shared airway and close collaboration between surgeon and anaesthetist in order to optimise operating conditions. Apnoeic oxygenation uses the principle of aventilatory mass flow to maintain oxygenation of pulmonary capillary blood under apnoeic conditions while minimising laryngeal movement. Concerns regarding accumulation of carbon dioxide and resultant acidaemia have limited the use of the technique. We performed a prospective study of low‐flow apnoeic oxygenation for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Animal experiments that may simulate these effects are not applicable due to completely different airway shapes. Further, since apneic oxygenation was detected long ago [ 15 , 16 ], and applied in multiple studies before [ 17 , 18 ] a technical simulation was to our opinion an acceptable tool to examine the hypotheses. However, as mentioned before, further clinical studies are mandatory to assess gas flows more precisely that on one side may be beneficial in avoiding arterial oxygen desaturation and on the other side do not result in excessive turbulences and thus gas mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments that may simulate these effects are not applicable due to completely different airway shapes. Further, since apneic oxygenation was detected long ago [ 15 , 16 ], and applied in multiple studies before [ 17 , 18 ] a technical simulation was to our opinion an acceptable tool to examine the hypotheses. However, as mentioned before, further clinical studies are mandatory to assess gas flows more precisely that on one side may be beneficial in avoiding arterial oxygen desaturation and on the other side do not result in excessive turbulences and thus gas mixing.…”
Section: Discussionmentioning
confidence: 99%
“…17 We are experienced in the use of low-flow apnoeic oxygenation via endotracheal catheter in ENT microlaryngoscopy. 18 The use of low-flow apnoeic oxygenation via the transtracheal jet catheter was added to our technique after we found it to be a successful temporising measure during initial surgical debulking of a large, obstructing laryngeal tumour. When there is a major degree of airway obstruction, the repeated high-pressure alarms and automatic interruption of ventilation by the jet ventilator can be sufficient to prevent adequate ventilation and oxygenation of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…There is a scientific body of evidence that hypoxemia can be prevented by deep insufflation of oxygen in the laryngeal space and trachea during apneic episodes [9][10][11][12]. Mitterlechner et al reported that oxygen saturation in a test-lung of a manikin remains significantly higher when using a specific laryngoscope blade designed for laryngeal oxygen insufflation, compared to nasal oxygen insufflation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mitterlechner et al reported that oxygen saturation in a test-lung of a manikin remains significantly higher when using a specific laryngoscope blade designed for laryngeal oxygen insufflation, compared to nasal oxygen insufflation [9]. Additionally, O'Loughlin et al showed that low-flow tracheal apneic oxygenation during microlaryngoscopy under general anesthesia allowed a successful conduction of surgical procedures and also impeded the increase of carbon-dioxide levels [11]. However, while oxygenation concepts approaching deeper anatomical airway structures are scientifically proven for unexpected difficult airways [13], evidence for apneic laryngeal oxygenation during elective fiberoptic intubation is scarce.…”
Section: Introductionmentioning
confidence: 99%